The Cooperativism functions in the different contextual frameworks: Analysis of the cooperative work sector in Villa María, province of Cordoba, Argentina (1989-2015) - Aminahuel, Aimé (Cooperativismo & Desarrollo, 2021)
Argentine cooperativism in its different subtypes and classifications, throughout Argentine history, assumed new and diverse socio-economic functions, several of the functional modalities in many cases were linked to the contextual economic dynamics and the possibilities and opportunities that arise. they opened these organizations at every juncture in socio-economic history. In this sense, this writing proposes to analyze the reconfigurations that went through -specifically-, the work cooperativism in terms of its functions and activities, from 1989 to 2015, in light of the transformations of the political economy of Argentina . In this way, the article aims to demonstrate the repercussions of the different accumulation models and contextual frameworks, at the national level, on the functions assumed by territorial organizations on a local scale such as cooperatives. This, from the approach of a case study: the work cooperatives in the city of Villa María, province of Córdoba. For such purposes, the methodology used was the survey of specialized bibliography, the documentary analysis of newspapers, national laws, official INAES documents and the systematization and construction of information from data provided by the Municipality of Villa María, Federations and Confederations of work cooperatives of the Argentine Republic. It is concluded that the work cooperatives transformed their functional modalities based on the changes in the different accumulation models in Argentina, throughout the years analyzed.
Keywords: cooperatives; organizational change; political economy; work cooperatives; argentine cooperatives